Due tipi di politica monetaria - J.C.R. DOW (Moneta e Credito, 2013)
The article traces the origin, development and effectiveness of two types of monetary policy. These are the 'demand management' approach, which uses monetary instruments as a means of maintaining policy, and the 'monetary targets' approach. The United Kingdom has moved from favouring the latter approach to the former, and the reasons behind this change of attitude are discussed. In addition the experiences of Italian governments and monetary policies are outlined.